2019
DOI: 10.1111/all.13732
|View full text |Cite
|
Sign up to set email alerts
|

The global incidence and prevalence of anaphylaxis in children in the general population: A systematic review

Abstract: Background:Despite an increasing number of publications from individual countries and regions, there is still no systematic review of the global epidemiology of anaphylaxis in the general paediatric population. Methods:We conducted a systematic review, using a protocol registered and published with the international prospective register of systematic reviews (PROSPERO).Results were reported following PRISMA guidelines. The search strategy was designed in Medline (ovid) and modified for Embase (ovid) and PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
87
3
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 41 publications
10
87
3
13
Order By: Relevance
“…Patients develop urticaria, angioedema or anaphylaxis within seconds to the first hour after taking one NSAID or NSAIDs from the same group, while tolerating others nonrelated . Mostly involved drugs are pyrazolones, paracetamol, diclofenac and ibuprofen .…”
Section: Phenotypes In the Eaaci Classificationmentioning
confidence: 99%
“…Patients develop urticaria, angioedema or anaphylaxis within seconds to the first hour after taking one NSAID or NSAIDs from the same group, while tolerating others nonrelated . Mostly involved drugs are pyrazolones, paracetamol, diclofenac and ibuprofen .…”
Section: Phenotypes In the Eaaci Classificationmentioning
confidence: 99%
“…[1][2][3] Asthma affects 9%-18%, 4,5 and allergic rhinitis (AR) affects up to 40% of children. 6 Food allergy (FA) is an epidemic among children in Westernized countries [7][8][9] and significantly impairs quality of life. 10,11 Between 15 and 40% of children with FA have experienced a severe, life-threatening allergic reaction and 30% report allergies to multiple foods.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the burden of anaphylaxis was thought to be lower in Asia and different from the West in terms of varying age distribution, anaphylaxis triggers and low usage of adrenaline auto-injectors (AAI) as first-line treatment 6,7 . However, a more recent study suggested that children of Asian ethnicity born in Australia may conversely be at higher risk of anaphylaxis compared to other ethnicities 8 . This discrepancy highlights the need for more accurate estimates of the true anaphylaxis burden in Asian countries.…”
Section: Introductionmentioning
confidence: 98%